Energy harvesting from charged conical nanopore with salinity and temperature gradient. (January 2023) - Li, Changzheng; Liu, Zheng; Wang, Yaofeng; Ali, Asad; Tian, Zhi Qun
Highlights: An energy harvesting system from charged conical nanopore with coupled salinity and temperature gradient is proposed. An interesting completive mechanism between the concentration gradient and temperature gradient effect was found, which determined the output performance. The enhancement of negative temperature difference on output power is more significant compared with positive temperature difference. The research results provide useful information for the design and optimization of energy devices. ABSTRACT: Renewable energy has been received more attention with the increasingly serious energy crisis. In this paper, an energy harvesting system from charged conical nanopore with coupled salinity and temperature gradient is proposed. The results show that the obtained maximum power increases first and then decreases as the concentration difference increases. Particularly, the enhancement of negative temperature difference (NTD) on maximum output power and the corresponding energy conversion efficiency is more significant compared with positive temperature difference (PTD) due to the simultaneous increase of short circuit current and open circuit voltage. Besides, the maximum output power is larger when the low concentration reservoir is connected to the tip end of the conical nanopore. The obtained maximum optimal value is about 0.22 pW. In the further investigation of a temperature gradient, we found that the short circuit current, open circuit voltage, and maximum output power show the approximately linear thermal response characteristics as the temperature difference is increased. Besides, an interesting competive mechanism between the concentration gradient effect and temperature gradient effect is found, which determines the prior conical nanopore orientation. The related research results provide useful information for the design and optimization of energy devices.